2013
DOI: 10.1177/1076029613490827
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Red Cell Distribution Width With the Presence and Severity of Preeclampsia

Abstract: Our study results revealed that RDW levels were associated with both the presence and the severity of preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
51
2
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 25 publications
11
51
2
13
Order By: Relevance
“…They are the first blood cells responding to inflammation [4]. Kurt et al, reported higher neutrophil counts in preeclamptic patients, implying the presence of an increased inflammatory state [9]. Our findings are consistent with their results as we detected the mean neutrophil count in the first trimester to be significantly higher in the group with preeclampsia.…”
Section: Discussionsupporting
confidence: 92%
“…They are the first blood cells responding to inflammation [4]. Kurt et al, reported higher neutrophil counts in preeclamptic patients, implying the presence of an increased inflammatory state [9]. Our findings are consistent with their results as we detected the mean neutrophil count in the first trimester to be significantly higher in the group with preeclampsia.…”
Section: Discussionsupporting
confidence: 92%
“…The mean RDW and MPV were significantly low in preeclampsia group than the control group in our study, conflicting with the results of previous studies which have performed the CBC test after the diagnosis of preeclampsia 2,11,17 . However, in a study designed similar to ours, Myatt et al have reported higher first trimester MPV levels in patients who later developed preeclampsia 20 .…”
Section: Discussioncontrasting
confidence: 99%
“…Kurt et al and Oylumlu et al have reported higher WBC counts and neutrophil counts in preeclamptic patients, implying that there is an increased inflammatory state 11,18 . The relation between increased WBC and preeclampsia has been explained by increased inflammation in these patients.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Erdoğan et al found no association between RDW levels and gestational diabetes mellitus [24]. Kurt et al found that RDW was associated with preeclampsia and with severity of the disease [25] .Otherwise Abdullahi et al could not find an association between serum RDW level and the presence of preeclampsia [26]. However, little is known and there is no study about if there is an association between RDW level and ICP.…”
Section: Discussionmentioning
confidence: 99%